PM flux-reversal machine for wind energy application - Bharathi, Manne; Prasanth, I. S. N. V. R.; Devi, Tellapati Anuradha; Kumar, Malligunta Kiran; Kumar, D. Ravi; Reddy, Ch. Rami (International Journal of Applied Power Engineering (IJAPE), 2024)
Currently, attempts are being made to harness wind energy by means of non-conventional electrical machines such as flux reversal machines (FRM). The main advantage of the FRM, when compared with existing synchronous generators (SG), is that all the active parts like PMs and armature windings are mounted on the stator part, whereas leaving the rotor has simple and robust. In this study, the three-phase 6/8-pole flux reversal generators (FRGs) are selected, sized, designed, and analyzed using finite element analysis (FEA). The working principle, choice of stator and rotor poles, and machine design dimensions evaluation (analytical sizing procedure), as well as relevant performance details are discussed in this paper. This study is used to analyze, a popular 6/8 pole, 0.8 kW, 50 Hz, and examine the suitability for the wind energy applications in terms of torque and power density, torque ripple, power factor, and cogging torque under 2D finite element analysis (FEA). The analysis provides an update on the current state-of-the-art and as well as future thrust areas of research necessary to bridge the gap on what is still desired for the practical application of FRMs for wind energy.